Pengaruh Teologi Ibadah Kontekstual dan Pemuridan terhadap Pertumbuhan Jemaat - Ivone Sri Wengkau; Tonny Andrian Stefanus; Ester Yunita Dewi (STIKAS Santo Yohanes Salib Kalimantan Barat, 2024)
This research examines the application of contextual theology in the organisation of worship and the discipleship process as an effort by the church to remain relevant in the face of social and cultural dynamics and the times. Through a comprehensive literature review, this research integrates various theories and models, including translation, anthropology, praxis, synthetic, and transcendental models, to reveal how the church can translate the teachings of the Christian faith adaptively and thoroughly. Contextualised worship does not only serve as a religious ritual, but also as a means of interaction between faith and the daily life of the congregation, thus encouraging active engagement and continuous spiritual growth. In addition, structured and holistic discipleship has proven effective in shaping character, faith maturity, and spiritual leadership, through the integration of spiritual, intellectual, and emotional aspects. The research also discusses the evolution of worship practices from the Old Testament to the New Testament, as well as identifying contemporary challenges such as the shift between traditional and modern worship. The results show that the implementation of church principles that are constantly renewed is key to success in maintaining fidelity to biblical values while remaining responsive to changing times. Future research recommendations include empirical studies across different cultural backgrounds, comparative analysis of contextual worship models, evaluation of discipleship programmes, and exploration of technology integration in worship settings. The findings make a significant contribution to the development of church practices that are inclusive, adaptive, and able to build vibrant communities of faith that are responsive to today's global challenges. The research also highlights the importance of inter-generational dialogue and community strengthening through innovative ministry activities, thereby encouraging positive social transformation and supporting the sustainability of the church's mission in an era of complex globalisation. The findings affirm the commitment of the real church.